Referral for Intensive Home Treatment or Psychiatric Inpatient Care? A Retrospective, Observational Comparison of Patient and Process Characteristics - van Asperen, G. C. Roselie; Wierdsma, André I.; de Winter, Remco F. P.; Mulder, Cornelis Lambert (Frontiers in Psychiatry, 2022)
Introduction: Intensive home treatment (IHT) is intended to prevent the (mostly voluntary) admission of mentally ill patients by providing intensive care in their domestic environment. It requires approaches to referral that ensure the delivery of the best possible acute care. Indications for referral may be improved by greater understanding of the clinical profiles of patients referred for IHT and of those referred for inpatient care. As such understanding may also further the development of IHT and innovations within it, we compared the patient and process characteristics associated with IHT referral for those associated with inpatient care. Methods: This observational, explorative study was conducted from 2016 to 2019. Patients aged 18 years and older were assessed by the emergency psychiatric outreach services in the greater Rotterdam area (Netherlands). Anonymized data were used to compare patient and process characteristics between patients referred for IHT and those admitted voluntarily. Patient characteristics included gender, age, cultural background, living situation and main diagnosis. Additional the case mix was measured using the Severity of Psychiatric Illness (SPI) scale. Process characteristics included psychiatric history, the total number of contacts with the emergency psychiatric outreach services, assessments during office hours, place of assessment, referrer, and the reason for referral. Using multiple logistic regression analysis, the patient and process characteristics associated with IHT referral were compared with those associated with voluntary admission. Results: Patient characteristics: Referral for IHT rather than voluntary admission was associated with higher motivation for treatment and better family involvement. Process characteristics: Referral for IHT rather than voluntary admission was associated with assessment by the crisis services within office hours, no mental health treatment at the time of referral, and referral by a family doctor. Discussion: IHT in a specific Dutch setting seems to function as an intensive crisis intervention for a subgroup of patients who are motivated for treatment, have social support, and are not in outpatient treatment. The patient and process characteristics of patients referred for IHT should now be studied in more detail, especially the role of the family members involved.